FILSAFAT DAN TEOLOGI:: MENEMUKAN PERSENYAWAAN EPISTEMOLOGI MELALUI GAGASAN FILSAFAT KEILAHIAN - Djaga, Chrisnasius; Labaka, Albri (Jurnal Teologi RAI, 2025)
Philosophy and theology are two disciplines that share a close historical and conceptual relationship, despite employing different approaches to understanding truth and knowledge. This study aims to examine the epistemological dualism between philosophy and theology to identify a convergence point, referred to as divine philosophy. The research employs a qualitative method with a literature-based approach, focusing on a conceptual analysis of the relationship between philosophy and theology from an epistemological perspective. The findings indicate that philosophy and theology often exist in epistemological tension. From an epistemological standpoint, the study emphasizes the integration of reason and faith as two complementary sources of knowledge: reason interprets revelation and empirical experience logically. In contrast, faith provides certainty and moral orientation toward divine truth. Divine philosophy emerges as a point of convergence that bridges rational and transcendental dimensions, proving relevant for critical and reflective theological education. Moreover, philosophy and theology mutually reinforce each other in shaping Christian values: philosophy offers a rational foundation for faith, whereas theology provides spiritual guidance that directs moral and existential action. This approach enables the development of a holistic, rational, reflective, and transformative faith, while also facilitating academic dialogue between contemporary philosophical and theological traditions.